Ultrasonic scissors decrease postoperative bleeding complications in mastectomy: A retrospective multicenter cohort study on 728 patients. Issue 1 (January 2023) - Tamminen, Anselm; Huttunen, Tuomas; Meretoja, Tuomo; Niinikoski, Laura; Koskivuo, Ilkka
Abstract: Introduction: The aim of this study was to evaluate the rate of postoperative bleeding complications (primary outcome) and any other surgical complications (secondary outcome) in mastectomy between two surgical instruments, ultrasonic SonoSurg® scissors (US) and traditional electrocautery (EC). Materials and methods: In total 728 patients undergoing mastectomy in two adjacent university hospitals were retrospectively evaluated in terms of postoperative bleeding episodes, surgical site infections, skin flap necrosis, and any reoperations for 30 postoperative days. A propensity score matching was performed to acquire balanced groups. Patients consuming medications affecting hemostasis were excluded from the study. A multivariable logistic regression analysis was conducted to define the odds ratio (OR) for each complication separately. A cost analysis was performed. Results: The rate of postoperative bleeding complications was significantly lower in patients operated with US (0.3% vs 11.5%, OR 0.020, 95% CI 0.034–0.14) when compared to EC. The rate of surgical site infections (OR 0.65, 95% CI 0.35–1.23) was similar with both instruments, but there were less skin flap necroses (OR 0.35, 95% CI 0.13–0.98) in US group. For any reoperation, the OR for US was 0.13 (95% CI 0.046–0.39), mainly due to the lower number of acute bleeding complications. Even though the US instrument is more expensive than EC, the total cost of the treatment is lower in patients operated with US (3419 vs. 3475 euro). Conclusions: US seems to be associated with a lower risk of bleeding complications in mastectomy.